Penerapan Hukum Adat Terkait Sengketa Tanah Wida Antara Masyarakat Kampung Lawir Dan Masyarakat Kampung Kakor Kecamatan Langke Rembong Kabupaten Manggarai Nusa Tenggara Timur - Thoe, Maria Suryati Dorman; Mauritsius, Darius; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2025)
This empirical legal research investigates a land dispute in Indonesia between the Lawir village community (descendants of Rona) and the Kakor village community (descendants of Wina), originating from a land grant to Wina upon her marriage. The study identifies the factors causing this potential conflict and examines the provisions of customary law in its resolution. Data was collected through interviews and literature review, and analyzed descriptively-qualitatively. The findings reveal that the dispute is triggered by the Kakor community's desire to sell the land, the absence of formal ownership documents, and the Lawir community's intent to reclaim the land for public facilities. The customary law resolution involves the Traditional Elder mediating through a process called